Promoting local vegetable and fruit consumption among pre-school children at a child development day care centre - C. Namyota (2019)
© All Rights Reserved. A quasi-experimental study aimed to improve vegetable and fruit consumption among preschool children aged 3-5 years old enrolled at two child development day care centres. Children were divided into two groups, an intervention-and comparison group. There were 43 cases in each group. The intervention group received the comprehensive program on promoting local vegetable and fruit consumption consisting of an activity series of 3 packages: awareness package, product development package, and reinforcement package, which were implemented together at the same time. The data were collected using a 24-hour dietary recall and food frequency questionnaire. The achievement of the program was analysed by comparing the amounts of vegetable and fruit consumed in the intervention and comparison groups using analysis of covariance (ANCOVA) under general estimating equations models (GEE). The results showed that intervention group consumed vegetable and fruit more than the comparison group by 1.78 serving (95% CI = 1.36 to 2.20, p-value < 0.001). It is concluded that there was increase of vegetable and fruit consumption at an early age. This program using local vegetable and fruit could be introduced to child development day care centres throughout Thailand.